The effectiveness of multicultural-based hand puppet book media in enhancing elementary students' tolerance character - Atika Susanti; Abdul Muktadir; Pratiwi Pujiastuti; Nady Febri Ariffiando (DWIJA CENDEKIA: Jurnal Riset Pedagogik, 2025)
This study aims to determine the effectiveness of the multicultural-based Hand Puppet Book media in enhancing the tolerance character of elementary school students. A quantitative approach was employed, using pretests and posttests to collect data. The research subjects were fourth-grade students from three schools in Depok District: Percobaan 2 Depok, Deresan, and Caturtunggal 3. Data analysis involved several stages of statistical tests, starting with a normality test to ensure normal distribution, followed by a homogeneity test to check for equality of variances among groups. An independent sample t-test with a significance level of 0.05 was then used to evaluate significant differences between the experimental and control groups. The results indicate that the multicultural-based Hand Puppet Book media is effective in improving the tolerance character of students. This is reflected in the gain scores: 0.08 (low) for the control class, 0.37 (medium) for experimental class I, and 0.39 (medium) for experimental class II. The independent sample t-test showed significant results of 0.041 between the control and experimental class I, and 0.030 between the control and experimental class II (sig < 0.05). Consequently, the multicultural-based Hand Puppet Book media proves to be an effective tool for fostering students' tolerance character.